Prophetic communication for strengthening religious life among female inmates in Paledang prison - Pambayun, Ellys Lestari; Kadri, Wahab Nur; Faraj, Muhammad Al-Husaini; Muyazanah, Agustriani; Purwitasari, Ira (Jurnal Kajian Komunikasi, 2025)
Background: Women in prisoners endure ongoing prejudice and objectification, issues that are intensified by the absence of a substantial religious life. At the Class II Correctional Institution in Paledang, Bogor, prophetic communication transcends mere imitation of the prophet’s communicative methods, ‘dawah,’ or ‘Islamic communication’; it encompasses efforts to emulate prophetic objectives, particularly in the context of shaping religious practices among female inmates, which remains inadequately explored. Comprehending its impact is crucial for fulfilling convicts’ spiritual and therapeutic requirements. Purpose: This study aimed to analyze the application of prophetic communication within the religious practices of female inmates in the Class II Paledang prison in Bogor. Methods: A phenomenological method was utilized to investigate the informants’ subjective awareness and interpretive experiences. The data collection was comprised of in-depth interviews, observations, and document analysis to thoroughly comprehend inmates’ religious experiences. Results: The results underscore three facets of prophetic communication: The humanistic aspect features structured religious programs; however, insufficient facilities impede optimal worship, and religious communication is restricted to communal prayers and spiritual visits; In the liberation aspect, initiatives promoting prophetic values like love and tolerance exist, yet numerous inmates remain disengaged; In the transcendence aspect, inmates are urged to cultivate Islamic spirituality. Conclusion: Prophetic communication can confront the spiritual issues inmates face, yet infrastructural limitations, inconsistency, and individual crises of faith hinder its efficacy. Implications: This study theoretically contributes to the discourse on prophetic communication in correctional environments and practically underscores the significance of structured religious guidance to improve inmates’ spiritual well-being and rehabilitation. This research is crucial for communication studies since it can provide new insights, particularly in critical theory for inmates, cross-cultural communication, spiritual communication, and gender communication.